Study of dentinal adhesives compatibility using histological analysis - Neusa Pereira Machado; Marcos Ribeiro Moysés; Alessandro Antônio Costa Pereira; Luciano José Pereira; José Carlos Rabelo Ribeiro (Universidade Estadual de Campinas, 2016)
The objective of this study was to verify the biocompatibility of three different dental adhesives (Single Bond, Clearfil SE Bond and Prime & Bond NT). Thirty-six male rats (Rattus norvegicus, Holtzman) received two subcutaneous implants in the region of their backs. Artificial sponges containing the adhesive material were placed in the cavities and they were polymerized before the surgical site was sutured. As a control, one group was implanted with sponges containing water. Each rat received two implants containing the same adhesive; consequently each group consisted of 9 rats with two implants, resulting in 18 samples per group. After 7, 15 and 30 days, 3 animals of each group were killed and the tissues containing the sponges were analyzed by microscopy. The results showed a great similarity between the control group and the Single Bond implanted tissues, followed by the Clearfil SE Bond and Prime & Bond NT. The Prime & Bond NT adhesive system appeared to show less biocompatibility when compared with the other two tested materials.